Bioprospecting the African Renaissance: The new value of muthi in South Africa - Reihling Hanspeter CW (BMC, 2008)
Abstract This article gives an overview of anthropological research on bioprospecting in general and of available literature related to bioprospecting particularly in South Africa. It points out how new insights on value regimes concerning plant-based medicines may be gained through further research and is meant to contribute to a critical discussion about the ethics of Access and Benefit Sharing (ABS). In South Africa, traditional healers, plant gatherers, petty traders, researchers and private investors are assembled around the issues of standardization and commercialization of knowledge about plants. This coincides with a nation-building project which promotes the revitalization of local knowledge within the so called African Renaissance. A social science analysis of the transformation of so called Traditional Medicine (TM) may shed light onto this renaissance by tracing social arenas in which different regimes of value are brought into conflict. When medicinal plants turn into assets in a national and global economy, they seem to be manipulated and transformed in relation to their capacity to promote health, their market value, and their potential to construct new ethics of development. In this context, the translation of socially and culturally situated local knowledge about muthi into global pharmaceuticals creates new forms of agency as well as new power differentials between the different actors involved.